A DESCRIPTIVE ANALYSIS OF ENGLISH INDONESIAN CODE SWITCHING SPOKEN BY THE TEACHER IN THE FIRST GRADE OF MTsN MODEL MAKASSAR - Nur Aliyah Nur (ETERNAL (English, Teaching, Learning and Research Journal), 2016)
The research aims to analyse the English Indonesia Code Switching Spoken by the Teacher in First Grade of MTsN Model Makassar. The principal issue into several subproblems or research questions such as 1) What are grammatical aspects of code switching in English Indonesian code switching spoken by the teacher in the first grade of MTsN Model Makassar?. 2) What are sosiolinguistic aspects of code switching in English Indonesian code switching spoken by the teacher in the first grade of MTsN Model Makassar?, and 3) What is the function of code switching in English Indonesian code switching spoken by the teacher in the first grade of MTsN Model Makassar?. The study was designed in the form of qualitative descriptive study. The subject in this study wasone of English teachers in the 7th grade of MTsN Model Makassar who teaches the VII.11 class. The data were collected by using the methods of recording and writing on note of what teacher said in teaching learning process, then collected it and classified based on grammatical aspect of code switching, sociolinguistic aspect, and the function (phatic function) of code switching. A grammatical focuses on the structural aspect of code switching. While, a sociolinguistic approach is concerned with the role of social factors of code switching. The result of this research showed that the grammatical aspect of code switching are extrasentential/tag switching, intersentential switching, and intra word of code switching. Sociolinguistic aspects of code switching are situational and metaphorical switching. The function of code switching are referential function, directive function, phatic function and metalingustic function. But this thesis only focused on phatic function to clarify or emphasize a message. The achievement of this research can be used to make easier in teaching foreign language and can be used as additional source and also can develop code switching field in the next research.